2008
DOI: 10.1124/jpet.107.133348
|View full text |Cite
|
Sign up to set email alerts
|

Lorcaserin, a Novel Selective Human 5-Hydroxytryptamine2C Agonist: in Vitro and in Vivo Pharmacological Characterization

Abstract: 5-Hydroxytryptamine (5-HT) 2C receptor agonists hold promise for the treatment of obesity. In this study, we describe the in vitro and in vivo characteristics of lorcaserin [(1R)-8-chloro-2,3,4,5-tetrahydro-1-methyl-1H-3 benzazepine], a selective, high affinity 5-HT 2C full agonist. Lorcaserin bound to human and rat 5-HT 2C receptors with high affinity (K i ϭ 15 Ϯ 1 nM, 29 Ϯ 7 nM, respectively), and it was a full agonist for the human 5-HT 2C receptor in a functional inositol phosphate accumulation assay, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
317
5
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(341 citation statements)
references
References 49 publications
14
317
5
5
Order By: Relevance
“…Maximum care was given in order to avoid stress during the oral supplementation of vitamin D 3 . Rats underwent 14 d of treatment, so that they were habituated to vitamin D 3 supplementation (14,15) . The last dose of vitamin D 3 and insulin was given 24 h before killing to minimise stressinduced endocrine changes due to oral administration.…”
Section: Methodsmentioning
confidence: 99%
“…Maximum care was given in order to avoid stress during the oral supplementation of vitamin D 3 . Rats underwent 14 d of treatment, so that they were habituated to vitamin D 3 supplementation (14,15) . The last dose of vitamin D 3 and insulin was given 24 h before killing to minimise stressinduced endocrine changes due to oral administration.…”
Section: Methodsmentioning
confidence: 99%
“…Based on experimental and human studies, the 5-HT2C receptor has been identified as a possible target for anti-obesity drugs [338]. Indeed, the 5-HT2C agonist lorcaserin (APD356) has been identified in rodents and humans to reduce food intake [344,345]. Lorcaserin has relatively few side effects (but 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 27 could be carcinogenic in rats) and has been approved in 2012 by the FDA for long term treatment of obesity [60,346].…”
Section: Serotonin and The Pharmacotherapy Of Obesitymentioning
confidence: 99%
“…44 5-HT 2C knockout mice are obese and insulin resistant; the cause of their obesity is hyperphagia, not altered metabolism. 45 One mouse model suggests that 5-HT 2C signaling may also enhance glucose tolerance independently of its effect on body weight. 46 The 5-HT 2B receptor, by contrast, is expressed on cardiac cells and has been implicated as the cause of fenfluramine-associated valvulopathy and pulmonary hypertension.…”
Section: Lorcaserinmentioning
confidence: 99%
“…47 Avoiding 5-HT 2A crossreactivity is also important, as this receptor is implicated in psychosis. 45 Despite the homology of these 3 receptors, lorcaserin activates 5-HT 2C with 18-fold selectivity over 5-HT 2A and 104-fold selectivity over 5-HT 2B in in vitro assays. 45 It has no appreciable activity at other serotonin receptors or receptors for other biogenic amines.…”
Section: Lorcaserinmentioning
confidence: 99%
See 1 more Smart Citation